2001
DOI: 10.1046/j.1471-4159.2001.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased infarct size and exacerbated apoptosis in the glutathione peroxidase‐1 (Gpx‐1) knockout mouse brain in response to ischemia/reperfusion injury

Abstract: Glutathione peroxidase is an antioxidant enzyme that is involved in the control of cellular oxidative state. Recently, unregulated oxidative state has been implicated as detrimental to neural cell viability and involved in both acute and chronic neurodegeneration. In this study we have addressed the importance of a functional glutathione peroxidase in a mouse ischemia/reperfusion model. Two hours of focal cerebral ischemia followed by 24 h of reperfusion was induced via the intraluminal suture method. Infarct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
157
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 35 publications
12
157
0
Order By: Relevance
“…GPX is an important component in the enzymatic defense system against the increase of free radicals (Crack et al 2001). In this study, the activity of glutathione peroxidase was reduced in lead treated groups (1.25 and 1.08 μg of GSH consumed/min/ mg protein, respectively for 1 week and 3 weeks lead treated groups) when compared to control group (1.34 μg of GSH consumed/min/mg protein).…”
Section: Methodsmentioning
confidence: 59%
“…GPX is an important component in the enzymatic defense system against the increase of free radicals (Crack et al 2001). In this study, the activity of glutathione peroxidase was reduced in lead treated groups (1.25 and 1.08 μg of GSH consumed/min/ mg protein, respectively for 1 week and 3 weeks lead treated groups) when compared to control group (1.34 μg of GSH consumed/min/mg protein).…”
Section: Methodsmentioning
confidence: 59%
“…The mechanism of the GPx1 protective role during brain I/R injury was recently a focus of a report by Crack et al (47). These authors demonstrated that GPx1 knockout mice display increased infarct size and exacerbated apoptosis compared with normal animals after MCA occlusion and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…GPX1 whose preferred substrate is hydrogen peroxide is the most abundant isoform found in the cytoplasm of nearly all mammalian tissues whereas GPX2 is an intestinal and extracellular enzyme. 82 GPX1 and GPX2 have been reported to protect against apoptosis induced by oxidative stress 83,84 ischemia/reperfusion injury 85 and doxorubicin 86 and to reduce pro-apoptotic Bax expression. 87 GPX4 (also known as phospholipid hydroperoxide glutathione peroxidase, PHGPX) overexpression has been reported to protect against oxidative stress-induced apoptosis.…”
Section: Figure 1 Apoptotic Signaling Pathways (See Text For Further mentioning
confidence: 99%